Conversations about conservation? Using social network analysis to understand energy practices. (March 2019) - Hamilton, Jo; Hogan, Bernie; Lucas, Karen; Mayne, Ruth
Abstract: This paper focuses on the use of mixed method social network analysis to understand how people's conversations might influence their energy practices and attitudes to energy conservation. Eighty-five qualitative interviews were conducted with individuals living in six different communities across the United Kingdom. Our analysis sheds new light on who people discuss energy issues with; the social contexts where energy is discussed; and some of the factors that 'open up' or 'close down' energy conversations. We compare the influence of low and zero carbon technologies, and other interventions, on people's energy conversations, and examine how perceived stigmas about discussing energy can be interpreted as 'policing' which can, in turn, inhibit further conversations about energy. We discuss the role that community-based organisations and other non-governmental agencies could play in potentially 'normalising' energy conversations, with the aspiration that such normalisation may influence the adoption of low and zero carbon practices.